2017
DOI: 10.1002/ehf2.12177
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization after intermittent levosimendan treatment in advanced heart failure patients: a meta‐analysis of randomized trials

Abstract: AimsIntermittent levosimendan administration has been suggested to improve survival in patients with advanced heart failure (AdHF). Quality of life is a key issue for AdHF patients and is negatively affected by frequent hospitalizations.Methods and resultsCENTRAL, Google Scholar, MEDLINE/PubMed, Scopus, and the Cochrane Central Register of clinical trials (updated 15/1/2017) were searched for randomized controlled trials investigating the effect of intermittent levosimendan administration in patients with AdHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
3
28
0
7
Order By: Relevance
“…The LION‐HEART data are in line with previous studies investigating the effect of repetitive administration of levosimendan and recent meta‐analyses, which demonstrated a reduction in hospitalization rate and mortality . Remarkably, LION‐HEART is the first multicentre trial in this field with positive results in both primary and secondary endpoints.…”
supporting
confidence: 86%
“…The LION‐HEART data are in line with previous studies investigating the effect of repetitive administration of levosimendan and recent meta‐analyses, which demonstrated a reduction in hospitalization rate and mortality . Remarkably, LION‐HEART is the first multicentre trial in this field with positive results in both primary and secondary endpoints.…”
supporting
confidence: 86%
“…15,16 Individual studies, including the LevoREP trial, 17 were, however, underpowered to provide definite conclusions regarding these endpoints. 15,16 Individual studies, including the LevoREP trial, 17 were, however, underpowered to provide definite conclusions regarding these endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Strategies to prevent rehospitalizations during this vulnerable period have not been consistently successful so far, although adherence to well-established medical therapies at optimal doses is considered essential. [15][16][17] However, some of these studies were open-label, single-centre studies, and even the largest, double-blind trial performed to date-LevoRep (NCT01065194) 17 -was limited to 120 patients. Intermittent or continuous inotropic therapy has also been tested, but, despite favourable haemodynamic and symptomatic improvement in pilot trials, 11 no positive effect on hospitalizations has been observed, and, in fact, there has been a trend towards a higher mortality risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent use of inodilators for long‐term symptomatic improvement or palliation has gained popularity, especially use of levosimendan, since the haemodynamic effect may last for >7 days after a 12–24 h infusion because of the pharmacologically active metabolite with a long half‐life . While meta‐analyses of several heterogeneous small trials of a repeated infusion strategy have suggested a positive effect on survival and a reduction in hospitalizations, such a survival effect has not been demonstrated in a single, adequately sized, prospective study. The LION‐HEART pilot study randomized 69 patients with advanced heart failure to placebo or levosimendan 0.2 µg/kg/min over 6 h every 2 weeks for 12 weeks .…”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%